Narrative analysis for Human Resources Research: The case of career change and development - Meirinhos, Viviana; Malta, Carla (Conferência - Investigação e Intervenção em Recursos Humanos, 2024)
Qualitative research methodologies emphasize the exploration, description, and comprehension of complex phenomena. In the field of Human Resources (HR), these methodologies provide insights into the social and organizational realities that are often difficult to capture through quantitative methods. This study proposes narrative analysis as a qualitative approach in HR research, highlighting its potential to uncover deeper meanings and offer a holistic understanding of employee experiences. The aim of this work is to present the narrative analysis methodology as a valuable tool for technical-scientific research in HR management and development, offering researchers a framework for its application. The narrative methodology is rooted in the understanding that stories are essential to human cognition, structuring experiences in a way that makes sense of reality (Bruner, 1991). Narratives are seen as a way to organize thoughts, events, and emotions over time, creating coherence and meaning from life experiences. In research, narratives are a powerful tool for interpreting how individuals and groups understand their roles within organizations, revealing their perspectives on challenges, successes, and the broader work environment (Polkinghorne, 2007). Within HR, the use of narrative analysis can offer deeper insights into organizational culture, leadership styles, employee motivation, and interpersonal relationships. By focusing on stories told by employees, narrative analysis reveals underlying patterns and themes that may be missed by more structured methods of data collection. These insights can support the development of HR strategies that align with the emotional and psychological needs of the workforce, contributing to stronger organizational outcomes (Czarniawska, 2011). This communication illustrate this research option with a study based on a qualitative, narrative approach, employing unstructured, in-depth narrative interviews to collect data. The focus was on exploring the lived experiences of HR professionals who have undergone career changes. The selection of participants aimed at capturing a broad spectrum of experiences, allowing for a diverse range of narratives to be analysed. By examining how participants structure their stories, the study aimed to understand the subjective factors that influence their career trajectories and experiences in HR management. This approach allowed for the identification of key emotional, social, and contextual elements that may not be evident through other research methods. [...]